ENTROPY METHOD AS CRITERIA FOR ANALYSIS A STEAM POWER PLANT (Journal of Engineering, 2009)
In this paper a theoretical analysis of South Baghdad and Dura power plant is carried out according to second law of thermodynamic depending on entropy (irreversibility coefficient or lost work) method instead of exergy (availability) method. In the used entropy method. The power plant is divided into main blocks ( boiler, turbine, condenser, and feed water heater and pumps ). The irreversibility losses and coefficient for each block are calculated and then the overall irreversibility and thermal efficiency of the plant are calculated. The results of this work are compared with previous results, that depending on exergy method. The comparison of results show that both methods give approximately the same results since both of them rely the 2nd law of thermodynamic. Entropy method is simple and intellectually and intuitively satisfying and giving direct relationship between components losses of power plant and its overall efficiency.